INTELLECTUAL CAPITAL AND FIRM PERFORMANCE OF BANKING SECTOR IN INDONESIA - Kondoy, Elfira Ira; Soewignyo, Fanny (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2023)
This study aims to evaluate the ability of intellectual capital to predict the performance of banking sector companies in 2018-2021 period using a purposive sampling method. Intellectual capital was measured using the Value-Added Intellectual Coefficient method which considers the elements of Human Capital Efficiency, Structural Capital Efficiency and Capital Employed Efficiency. The results of this study indicated that intellectual capital could predict company performance. The three elements of intellectual capital simultaneously influenced the performance of banking sector companies as measured by return on assets and 84% of the variation in company performance was determined by intellectual capital. Partially, Human Capital Efficiency and Capital Employed Efficiency had a significant positive effect on company performance which stated that the higher the Human Capital Efficiency and Capital Employed Efficiency the better the company performance, while Structural Capital Efficiency had a significant negative effect on company performance stating that the greater the investment in structural capital, the lower the company's performance. Furthermore, it was found that variations in Indonesian banking performance depended heavily on human resources (standardized beta = 0.729), followed by physical and financial assets (standardized beta = 0.207), and finally on structural capital (standardized beta = -0.098). The role of human resources was still very large in the Indonesian banking sector. This study had limitations; therefore, it is recommended for further research to add all non-bank financial sectors because a larger sample size is expected to provide better results. Furthermore, it is recommended that COVID-19 is added as a moderating variable.